Isolation and Analysis of Nucleotide Sequences of the 16S rRNA Gene of Pseudomonas aeruginosa Isolated from Clinical Samples - Atheer Abdulameer Raheem1 , Hasanain Khaleel Shareef1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Pseudomonas aeruginosa consider one of the opportunistic pathogens is able to infection almost all bodytissue as a result of having it a variety of virulence factors that contribute greatly to pathogenic events in thehost this bacterium has been responsible for 30% of pneumonia, 19% of urinary tract infections and 10%of bloodstream infections. And leads to nosocomial pathogens causing infections that usually develop lateduring hospital stay. Consequently the aim of this research was to classify and characterize P. aeruginosaisolated from various clinical samples from Iraqi patients by sequencing the 16S rRNA gene.